Impact of Postshock Transcutaneous Pacing on Chest Compression Quality during Resuscitation: A Simulation-Based Pilot Study - Wojciech Telec; Tomasz Kłosiewicz; Radosław Zalewski; Julia Żukowska-Karolak; Artur Baszko; Mateusz Puślecki (Emergency Medicine International)
Background. Successful defibrillation is commonly followed by a transient nonperfusing state. To provide perfusion in this stagnant phase, chest compressions are recommended irrespective of arrhythmia termination. Implantable cardioverters-defibrillators (ICD) used immediately after delivery of the shock are capable of pacing the heart, and this feature is commonly activated in these devices. Potential utility of external, transcutaneous postshock pacing in patients with SCA in shockable rhythms has not been determined. This study aimed at presenting an impact of a short-term external postshock pacing (ePSP) on a quality of chest compressions (CC) without compromising them. Methods. The study was designed as a high-fidelity simulation study. Twenty triple-paramedic teams were invited. Participants were asked to take part in a 10-minute adult cardiac arrest scenario with ventricular fibrillation. In the first simulation, paramedics had to resume compressions after each shock (control group). In the second, simultaneous with compressions, one of the rescuers started transcutaneous pacing (TCP) with a current output of 200 mA and a pacer rate of 80 ppm. TCP was finished after 30 seconds (experimental group). The primary outcomes were chest compression fraction (CCF), mean depth and rate of compressions, percent of fully recoiled compressions, and percent of compressions of correct depth and their rate. Results. In both experimental and control group, CCF, mean depth, and rate were similar (84.65 ± 3.67 vs. 85.45 ± 4.95, p=0.54; 55.75 ± 3.40 vs. 55.25 ± 2.73, p=0.63; 122.70 ± 4.92 vs. 120.80 ± 6.00, p=0.25, respectively). In turn, percent of CC performed in correct depth, rate, and recoil was unsatisfactory in both groups (51.00 ± 17.40 vs. 52.60 ± 18.72, p=0.76; 122.70 ± 4.92 vs. 120.80 ± 6.00, p=0.25, respectively). Small differences were not statistically significant. Moreover, appropriate hand-positioning was observed more frequently in the control group, and this was the only significant difference (95.60 ± 5.32 vs. 99.30 ± 1.59, p=0.006). Conclusion. This difference was statistically significant (p<0.01). Introducing an ePSP does not influence relevantly the quality of CC.